Clinical update: Eating disorders in children and young people - Bould, H; Newbegin, C; Stewart, A; Stein, A; Fazel, M (BMJ Publishing Group, 2017)
Eating disorders (ED) are a group of conditions in which negative beliefs about eating, body shape and weight accompany behaviours including restricting eating, binge eating, excessive exercise, vomiting and laxative use. In Anorexia Nervosa (AN), weight is “less than minimally expected”, dietary intake is restricted, and there are disturbances in the way weight and shape are experienced. Bulimia Nervosa (BN) comprises binge eating with compensatory behaviours aimed at reducing weight, such as vomiting or excessive exercise, while Binge Eating Disorder (BED) includes binge eating but without compensatory behaviours. In DSM-51, a new category “Other Specified Feeding or Eating Disorder” (OSFED) replaces EDNOS (Eating Disorder Not Otherwise Specified) for ED causing distress and impairment but not meeting full criteria for other diagnoses. Binge Eating Disorder (BED) has now been included and it is anticipated that ICD-11 criteria will be broad criteria consistent with DSM changes.